If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + 4x = 12 + 9x Solving -8 + 4x = 12 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -8 + 4x + -9x = 12 + 9x + -9x Combine like terms: 4x + -9x = -5x -8 + -5x = 12 + 9x + -9x Combine like terms: 9x + -9x = 0 -8 + -5x = 12 + 0 -8 + -5x = 12 Add '8' to each side of the equation. -8 + 8 + -5x = 12 + 8 Combine like terms: -8 + 8 = 0 0 + -5x = 12 + 8 -5x = 12 + 8 Combine like terms: 12 + 8 = 20 -5x = 20 Divide each side by '-5'. x = -4 Simplifying x = -4
| 5(2n-6)=-110 | | LA=3.14(r)(s) | | 4•/•2 | | 8=k+k | | P(X)=22.45 | | 4(5+6r)=116 | | (6-z)(4z-1)=0 | | 6x+15y+5=0 | | O(10)O(n)=2n-1 | | 6p+6+1=13 | | 2(b-1)=5b+1 | | 2(6x+3)=2(x+6) | | 9/0= | | 12y-4y=-128 | | -4=5n-n | | 8x+4=196 | | 4x+8=196 | | 30t+2.50=67.50 | | -92=-2-5(-2+4b) | | 1.64=x-45 | | 3/5x(-5/8)= | | 2*x^3-6*x+2=0 | | (11+a)+16= | | 4x-x+x=2+10 | | 3x-5=10x-56 | | 2(6x-6)=6(5x-5) | | 4a-2(a-5)=-2 | | 6t+t+40=180 | | b+75+2b=180 | | .5x^3-3x^2+1=0 | | 5m-7m+18=10 | | 3*log(x-1)=9 |